Tipping: has it becoming prevalent norms in Malaysia hospitality industry / Mohd Salehuddin Mohd Zahari … [et al.] - Mohd Zahari, Mohd Salehuddin; Abdul Patah, Mohd Onn Rashdi; Mohd Radzi, Salleh; Othman, Zulhan (Universiti Teknologi MARA (UiTM), Malaysia, 2011)
As tipping is consider a main source or additional income for millions of service personnel and closely related to behavioural and social economics perspective, it has continually received significant attention among the academic scholars since the last two decades. Many researchers agree that tipping is one the most efficient and effective ways in monitoring, rewarding effort of service workers, token of appreciation, complement or as an incentive for good service delivered. This non-legal required obligation although is not a social norm like in the United States and some of the European countries, but the practices are widely spread particularly in the tourism, hospitality and restaurant industry and becoming internationalized including in Malaysia. Despites not an institution and part of the Malaysian culture, tipping is becoming more widespread and acceptable in this country hospitality industry. The practice is unlikely to disappear instead will continue to increase from time to time. This research note besides reviewing the past studies on tipping, different countries practices but narratively emphasises and highlights the current practice in Malaysia scenario. In other words, this paper not only creating the first local literature but lay the groundwork for other Malaysian researchers to further look into this tipping issue from various perspectives in line with vigorous development of Malaysia tourism, hospitality and restaurant industry.